Perceptions of Clinical Decision-Making Skills among Saudi Nursing Students: A Comparative Study - AL-Dossary, Reem Nassar; Dorgham, Sherien Ragab Abdelsamed; Maniago, Jestoni Dulva (Journal of Health and Allied Sciences NU, 2019)
Introduction As complexities in healthcare and medical technology increase, nursing students and newly graduated nurses may often feel less confident and have fewer skills in decision-making than experienced nurses.Objective The main purpose of this article is to explore nurses’ perceptions of their clinical decision-making skills.Materials and Methods A comparative, cross-sectional design was used to conduct a study at a college of nursing in the Eastern Province of Saudi Arabia. The sample consisted of students (n = 139) enrolled in bridging (n = 72) and undergraduate (basic; n = 67) programs.Results Highly statistically significant differences were revealed between students in the bridging program and those in the undergraduate program. Those in the bridging program showed higher mean and median values than did undergraduate students, demonstrating better decision-making skills.Conclusion Students in the bridging program have better decision-making skills compared with students in the baccalaureate program.
Keywords: baccalaureate; bridging; clinical simulation; nursing education; cross-sectional; quality patient care